Together - Lyon, George Ella 1949-; Rosenberry, Vera (New York Orchard Books, 1989)
An illustrated poem about friendship and togetherness.
A Richard Jackson book--1st prelim. p.
Keywords: Children's poetry, American; Friendship -- Poetry; American poetry